2019
DOI: 10.3390/min9060345
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Mineralogical Knowledge in the Sustainability of Artisanal Gold Mining: A Mid-South Peru Case

Abstract: Mineralogy and gold processing techniques from several mining areas of the Nazca-Ocoña gold belt, Mid-South Peru, were investigated to assess the efficiency of gold extraction methods in relation to their mineralogy. The deposits from this belt are intrusion gold related to mineralization in quartz veins. Native gold occurs as micrometric grains encapsulated in pyrite and in minor amounts in other sulfides and quartz. Electrum is found mainly in fractures of pyrite and attains up to 35 wt. % Ag. In addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…Based on the information above and our observations, we suggest that San Juan de Chorunga, Misky, and San Cristóbal deposits have the same ore mineralogy and occurrence in the veins. Previous studies in Cháparra deposit showed that gold mineralization occurs in quartz veins related to a high quantity of iron oxyhydroxides and sulfides, mainly pyrite [16]. Our microscopy observations suggest that Cháparra and Mollehuaca deposits have similar vein mineralogy.…”
Section: Ore Mineralizationsupporting
confidence: 66%
See 3 more Smart Citations
“…Based on the information above and our observations, we suggest that San Juan de Chorunga, Misky, and San Cristóbal deposits have the same ore mineralogy and occurrence in the veins. Previous studies in Cháparra deposit showed that gold mineralization occurs in quartz veins related to a high quantity of iron oxyhydroxides and sulfides, mainly pyrite [16]. Our microscopy observations suggest that Cháparra and Mollehuaca deposits have similar vein mineralogy.…”
Section: Ore Mineralizationsupporting
confidence: 66%
“…The San Cristóbal veins are located close to San Juan de Chorunga and have similar Au and Ag contents. Figure 8 also includes EMP analyses of electrum grains from the Misky, Santa Filomena, San Cristóbal, Cháparra, and San Luis deposits [16]. Similar to these deposits, we observed that electrum from Mollehuaca and San Juan de Chorunga maintained a negative linear trend in Ag vs.…”
Section: Au-ag Bearing Mineralsmentioning
confidence: 52%
See 2 more Smart Citations
“…The mineralization consists in veins hosted in diorites and granodiorites from the Tiabaya Super-Unit. This deposit belongs to the intrusive-related type [2]. Mineralization is mainly found in NW-SE in veins of some tens of decimetres wide and dipping about 70 °.…”
Section: Extended Abstractmentioning
confidence: 98%